CSNY Crosby, Stills, Nash & Young - Doggett, Peter 1957- (Simon & Schuster, 2019)
Presents a biography focused on the formative and highly influential early years of rock's first supergroup, from their emergence at Woodstock in 1969 through their years as one of the most successful and culturally significant bands in American music
Keywords: Crosby, Stills, Nash & Young -- Musikgruppe; Geschichte 1968-; Crosby, Stills, Nash & Young; Rock musicians / United States / Biography; Rock musicians; United States; Biography; Biographies; Biografie